Scaffold-hopping for molecular glues targeting the 14-3-3/ERα complex - Markella Konstantinidou; Marios Zingiridis; Marloes A. M. Pennings; Michael Fragkiadakis; Johanna M. Virta; Jezrael L. Revalde; Emira J. Visser; Christian Ottmann; Luc Brunsveld; Constantinos G. Neochoritis; Michelle R. Arkin (Nature Communications)
Abstract Molecular glues, small molecules that bind cooperatively at a protein-protein interface, have emerged as powerful modalities for the modulation of protein-protein interactions (PPIs) and “undruggable” targets. The systematic identification of new chemical matter with a molecular glue mechanism of action remains a significant challenge in drug discovery. Here, we present a scaffold hopping approach, using as a starting point our previously developed molecular glues for the native 14-3-3/estrogen receptor alpha (ERα) complex. The novel, computationally designed scaffold is based on the Groebke-Blackburn-Bienaymé multi-component reaction (MCR), leading to drug-like analogs with multiple points of variation, thus enabling the rapid derivatization and optimization of the scaffold. Structure-activity relationships (SAR) are developed using orthogonal biophysical assays, such as intact mass spectrometry, TR-FRET and SPR. Rational structure-guided optimization is facilitated by multiple crystal structures of ternary complexes with the glues, 14-3-3 and phospho-peptides mimicking the highly disordered C-terminus of ERα. Cellular stabilization of 14-3-3/ERα for the most potent analogs is confirmed using a NanoBRET assay with full-length proteins in live cells. Our approach highlights the potential of MCR chemistry, combined with scaffold hopping, to drive the development and optimization of unprecedented molecular glue scaffolds.